Succinate/IL-1β Signaling Axis Promotes the Inflammatory Progression of Endothelial and Exacerbates Atherosclerosis - Xu, Jingwen; Zheng, Yabing; Zhao, Yaqing; Zhang, Yujiao; Li, Huilin; Zhang, An; Wang, Xuehan; Wang, Weizong; Hou, Yinglong; Wang, Jiangrong (Frontiers in Immunology, 2022)
Inflammation is an important driver of atherosclerosis. Succinate is a new extracellular inflammatory alarm released by activated macrophages. Succinate is sensed by succinate receptor 1 (Sucnr1) and then transferred to effector cells. It is worth exploring whether succinate is capable of facilitating the inflammatory response in atherosclerosis. In this study, we firstly found that arterial serum of Coronary Heart Disease (CHD) patients contained significantly higher succinate and interleukin (IL)-1β than Health control (HC) subjects, and succinate was positively correlated with IL-1β. As demonstrated by the in vitro study, succinate/hypoxia-inducible factor 1α (Hif)-1α/IL-1β signal axis existed and significantly facilitated the inflammatory program in human umbilical vein endothelial cells (HUVECs). Under the coculture, activated macrophages released succinate, which would be transferred to HUVECs via Sucnr1 and then activate Hif-1α to produce a greater amount of IL-1β. Likewise, the aortic sinus’s inflammatory phenotype was found to be more significant within Apoe-/- mice that were injected with succinate. Furthermore, Sucnr1 inhibitor (NF-56-EJ40) could significantly interrupt succinate/IL-1β signal in HUVECs and macrophages. As revealed by this study, glycolytic metabolism following the release of succinate could be found in atherosclerotic pathology, and succinate would drive succinate/IL-1β signal dependent on Sucnr1 and then exacerbate inflammatory responses. Sucnr1 might be a novel target for cutting off the transduction of succinate signal to prevent the inflammation of atherosclerosis.